TINGKAT DAYA TAHAN KARDIOVASKULER PADA ATLET PEKAN OLAHRAGA PROVINSI - Syahratul Annisa; Rusli Rusli; Sarifin G (Jurnal Ilara : Jurnal Hasil Penelitian, Aplikasi Teori, Analisa, Dan Pembahasan Kepustakaan tentang Keolahragaan, 2023)
This study aims to determine the level of cardiovascular endurance of athletes from Porprov Kab. Jeneponto. This research is a descriptive research. The data collection technique was carried out using the test method and measuring cardiovascular endurance with a multistage fitness test (bleep test) involving 15 samples of athletes from Porprov Kab. Jeneponto which consists of volleyball, sepak takraw, and swimming athletes. The results of this study indicate that the endurance of athletes from Porprov Kab. Jeneponto is in the good category, this is evidenced by the frequency distribution value in the good category as many as 11 athletes (73.3%), then in the very good category as many as 3 athletes (20%) at least in the special category as many as 1 athlete (6.7%) .